Good Life As a Social Movement Proposal for Natural Resource Use: The Indigenous Movement in Ecuador - Altmann, Philipp (Consilience, 2014)
The Ecuadorian indigenous movement has developed the concept of Good Life (Sumak Kawsay or Buen Vivir) as a conceptual weapon in order to defend the territories of indigenous nationalities as the movement itself defines them. Starting in 2002, petroleum exploitation in indigenous areas in the Amazon has been denounced as an attack against the principles of the traditional concept of Good Life. The introduction of the concept of Good Life allowed the local as well as the national indigenous organizations to define their vision of the country and society, while allowing easier coalitions with a growing Ecological Left. Good Life is not only a new content in the indigenous discourse, but also an instrument for social movement mobilization and coalition building. This text aims to offer a clearer idea of what the indigenous movement in Ecuador understands as Good Life, the development of the concept, the different contents and relations it has, and its strategic use in Ecuadorian politics.